#IAmNotAfraidToSayIt: Stories of Sexual Violence as Everyday Political Speech on Facebook - Lokot, Tetyana (AoIR Selected Papers of Internet Research, 2017)
The debate about the power and influence of networked publics often focuses on large-scale political events, activist campaigns and protest activity – the more visible forms of political engagement. On the other hand, digitally mediated activism is often questioned and sometimes derided as a lesser form of dissent, as it is easier to engage in, highly affective, and offers few assurances of sustainability of the change it calls for. But what about everyday political speech online, where social media platforms can contribute to a personalisation of politics? Can social media users express their views online and make a difference? This paper is an analysis of over 3,500 Facebook posts and a collection of other texts stemming from the ‪#‎ЯНеБоюсьСказати‬ (Ukrainian for #IAmNotAfraidToSayIt) online campaign that was started in the Ukrainian segment of Facebook in July 2016 by a local activist to raise awareness of how widespread sexual violence and sexual harassment are in the Ukrainian society. The paper argues that networked conversations about everyday rights and affective stories about shared experiences of injustice, underpinned by the affordances of social media platforms for sharing and discussing information and participating in everyday politics, can emerge as viable forms of networked activism and can have real impact on the status quo of an issue, both in the digital sphere and beyond it.